Vulnerabilidad a nivel de ecosistema de Páramo frente al Cambio Climático en la zona de Igualata Parroquia San Isidro, Cantón Guano Provincia de Chimborazo - Echeverría, Magdy (2017)
The present study has as purpose to establish an index and a level of vulnerability associated with Páramo ecosystem to the effects of climate change through the identification of the different hazards that could cause an impact on this system. To achieve a reliable and concise analysis was delimited the study area by three geographical approaches: ecosystem, data collected of carbon and bordering features, data both t emperature and current precipitation are generated based on climate models implemented by the Ministry of the Environment through meteorology Stations validated at the national level by the National Institute of Meteorology and Hydrology, also is achieved in the present study to analyze the variable precipitation through the meteorology station M390 (Urbina). Another variable considered in this study is the likely future climate where are used data provides by the Japanese Climate Model TL959. The vulnerability in this study is focused on the analysis of 8 indicators under the conceptualization of the 3 elements of vulnerability, ie; Exposure, sensibility and adaptability. It is necessary to take into account that is determined in the same way the potential impact as part of this process. The indicators are focused under the analysis of scales (1-3) for the analysis of the elements of vulnerability and (0-100) for Total vulnerability index. The study found an equivalent of vulnerability in the ecosystem of 62.5 which is considered as high level of vulnerability.